The ability of a low value on an early GCT to identify women not needing repeat testing in the second trimester. (12th December 2022) - Kuyoro, Olutunmike; McLaren, Rodney A.; Narayanamoorthy, Sujatha; Weedon, Jeremy; Minkoff, Howard
Abstract: Objective: To evaluate the predictive value of a low early glucose challenge test (GCT) in ruling out a subsequent diagnosis of gestational diabetes in the second trimester. Methods: This was a retrospective cohort study of women at a single clinic who had a normal early GCT between 2016 and 2020. Patients who did not have repeat screening in the late second trimester were excluded. Demographic data were extracted from the record. The primary outcome was a normal GCT or glucose tolerance test in the late second trimester. Logistic regression and receiver operator curves (ROC) were performed to assess the ability of the early GCT value to predict subsequent normal glucose screening. Results: Of the 532 pregnant persons with normal early GCT, 62 (11.7%) were subsequently diagnosed with gestational diabetes in the second trimester. None of the patients ( N  = 56), who had a GCT value less than 80 mg/dL were diagnosed with gestational diabetes in the second trimester. The prediction of subsequent normal screening using the early GCT on a ROC plot produced an area under the curve (AUC) of 0.67, 95% CI (0.60–0.74). Adding age, prior history of gestational diabetes and family history of diabetes mellitus to the prediction, only improved the AUC to 0.75, 95% CI (0.66, 0.82). Conclusion: Early GCT value was a fair predictor for normal second trimester glucose testing for gestational diabetes. However, high-risk patients with an early GCT value of less than 80 mg/dL may be able to forego repeat second trimester screening.